2004
DOI: 10.1177/001698620404800404
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Learning Behaviors Scale (LBS) Scores With Academically Talented Students: A Comparative Perspective

Abstract: In this study, teacher ratings of academically talented (AT) students on the Learning Behaviors Scale (LBS) were examined for evidence of reliability and validity in two cohorts attending a summer program. The LBS is a 29-item rating scale assessing learning behaviors related to academic success. Cohort 1 consisted of 387 students and Cohort 2 consisted of 287 students. The AT students’ scores were similar to scores of gifted and talented and high-IQ students in the normative sample, and reliability estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
(106 reference statements)
0
14
0
Order By: Relevance
“…ticipants' mean self-reported GPA in their home schools was 3.83 (SD = .37), and previous research on students in this program has indicated that the profile of the participants is more similar to students identified for gifted and talented education programs than students with high IQs who have not been identified (see Worrell & Schaefer, 2004). Participants were taking a wide variety of courses, including writing and language arts, lab sciences, math, and the arts.…”
Section: The Influence Of Instrumentality Beliefsmentioning
confidence: 91%
“…ticipants' mean self-reported GPA in their home schools was 3.83 (SD = .37), and previous research on students in this program has indicated that the profile of the participants is more similar to students identified for gifted and talented education programs than students with high IQs who have not been identified (see Worrell & Schaefer, 2004). Participants were taking a wide variety of courses, including writing and language arts, lab sciences, math, and the arts.…”
Section: The Influence Of Instrumentality Beliefsmentioning
confidence: 91%
“…Researchers and educators assess student perceptions to understand teacher effectiveness (e.g., Onwuegbuzie et al, 2007), students' learning preferences and behaviors (e.g., Worrell & Schaefer, 2004), and students' preferred learning environment (e.g., Gentry, Rizza, & Gable, 2001). Based on motivation theory, students' perceptions of their classroom experiences influence how much effort they put into classroom tasks, with more effort resulting in better learning and higher achievement (Wentzel, Wigfield, & Miele, 2009).…”
Section: Student Perceptions Of Classroom Experiencesmentioning
confidence: 99%
“…Schools often use locally developed scales, but they may use published scales such as the HOPE Teacher Rating Scale (Peters & Gentry, 2013) or the Scales for Rating the Behavioral Characteristics of Superior Students (Renzulli et al, 2013). Although some scholars (e.g., Robinson, Shore, & Enersen, 2007; Worrell & Schaefer, 2004) have concluded from their data that teachers can be reliable identifiers of giftedness, others have urged caution (e.g., Ford, Grantham, & Whiting, 2008; Siegle & Powell, 2004). Peer nomination (e.g., Cunningham, Callahan, Plucker, Roberson, & Rapkin, 1998), parent nomination (e.g., Lee & Olszewski-Kubilius, 2006), grades, and portfolios (e.g., Slade, 2012; VanTassel-Baska, Johnson, & Avery, 2002) also have been examined and advocated for as part of the screening and identification processes.…”
Section: Introductionmentioning
confidence: 99%